a) \(\left(x+1\right)\left(x+2\right)\left(x+3\right)\left(x+4\right)-8\)
\(=\left[\left(x+1\right)\left(x+4\right)\right]\left[\left(x+2\right)\left(x+3\right)\right]-8\)
\(=\left(x^2+5x+4\right)\left(x^2+5x+6\right)-8\)
\(=\left(x^2+5x+5\right)^2-1-8\)
\(=\left(x^2+5x+5\right)^2-3^2\)
\(=\left(x^2+5x+2\right)\left(x^2+5x+8\right)\)
b) \(xy\left(x-y\right)+yz\left(y-z\right)+zx\left(z-x\right)\)
\(=xy\left(x-y\right)+y^2z-yz^2+z^2x-zx^2\)
\(=xy\left(x-y\right)+z^2\left(x-y\right)-z\left(x-y\right)\left(x+y\right)\)
\(=\left(x-y\right)\left(xy+z^2-zx-yz\right)\)
\(=\left(x-y\right)\left[x\left(y-z\right)-z\left(y-z\right)\right]\)
\(=\left(x-y\right)\left(x-z\right)\left(y-z\right)\)
a) ( x + 1 )( x + 2 )( x + 3 )( x + 4 ) - 8
= [ ( x + 1 )( x + 4 ) ][ ( x + 2 )( x + 3 ) ] - 8
= ( x2 + 5x + 4 )( x2 + 5x + 6 ) - 8
Đặt t = x2 + 5x + 5
bthuc ⇔ ( t - 1 )( t + 1 ) - 8
= t2 - 1 - 8
= t2 - 9
= ( t - 3 )( t + 3 )
= ( x2 + 5x + 5 - 3 )( x2 + 5x + 5 + 3 )
= ( x2 + 5x + 2 )( x2 + 5x + 8 )
b) xy( x - y ) + yz( y - z ) + zx( z - x )
= x2y - xy2 + y2z - yz2 + zx( z - x )
= ( y2z - xy2 ) - ( yz2 - x2y ) + zx( z - x )
= y2( z - x ) - y( z2 - x2 ) + zx( z - x )
= ( z - x )( y2 + zx ) - y( z - x )( z + x )
= ( z - x )( y2 + zx - yz - yx )
= ( z - x )[ ( y2 - yx ) - ( yz - zx ) ]
= ( z - x )[ y( y - x ) - z( y - x ) ]
= ( z - x )( y - x )( y - z )